PHYSICS OF ISLAND-ARC VOLCANIC ACTIVITY - Zharinov S.Ye.; Dyomin S.S. (My University, 1990)
The problem of the heat source for island-arc volcanic activity is still unexplainable in the context of an assumed continuous subduction process. Adopting the general idea that the evolution of island-arc systems is an unsteady-state process, the authors have earlier suggested a qualitative description of one particular phase, namely that in response to a tectonic compression pulse. The results of our earlier numerical analysis are in good agreement with the geological, geophysical and seismologic data. The vertical displacements of the free surface in the model are consistent with the main relief forms encountered in the trench-arc-marginal sea system. The Benioff zone is treated in the model as a region of concentration of shear stresses caused by the redistribution of the tectonic load near the fault zone. This representation enables us to describe the nature of the seismicity and the structural characteristics of real seismic focus zones, including their two-layered structure and the occurrence of seismic anisotropy. In this paper we discuss the application of our model to the description of the physics of island-arc volcanic activity. Under our model, the ascent of magma from the zone of its generation to the surface is propelled by a steady extrusive pressure gradient, generated by the redistribution of externally-applied tectonic loads. The localization of the heat source on the boundary that we have identified and the geometry of the region of large extrusive gradients explain the origin of the volcanic belts of island arcs and their characteristic position (which is independent of the slope of the Benioff zone and of the rate of the putative subduction).